Chemical Composition and Antifungal Properties of Guava Leaf Extract (Psidium guajava L.) Against Pythium aphanidermatum, Chinese Kale Damping-Off Disease Pathogen - Maneechai, Suthira; Siphim, Thawanrat; Srisawad, Nattaya; Sutthisa, Waraporn (Trends in Sciences, 2024)
Damping-off disease represents a considerable hazard to the cultivation of Chinese kale (Brassica oleracea var. alboglabra), leading to seedling death and notable economic repercussions. This study explores the efficacy of guava leaf extracts, obtained through different extraction solvents, against Pythium aphanidermatum, a significant pathogen causing damping-off disease in Chinese kale (Pak Kha-naa) cultivation in Thailand. Guava leaf extract was obtained using different solvents: hexane, ethyl acetate and ethanol. Subsequently, the extract was diluted to concentrations of 1,000, 1,500 and 3,000 ppm to assessment the inhibitory effects on P. aphanidermatum utilizing the poisoned plate technique. Results revealed that only ethanol-extracted guava leaf extract at 3,000 ppm exhibited significant inhibition of P. aphanidermatum, achieving complete inhibition. At 1,500 ppm, ethanol-extracted guava leaf extract demonstrated inhibition comparable to carbendazim. Greenhouse trials further confirmed the efficacy of pre-planting seeds coating with ethanolic guava leaf extract at concentrations of 1,500 and 3,000 ppm in reducing damping-off disease incidence in Chinese kale. Chemical analysis of guava extract with GC-MS revealed the presence of 58 compounds in the hexane extract, with copaene, β-caryophyllene, calamenene and caryophyllene oxide being major constituents. The ethyl acetate extract contained 53 compounds, including β-caryophyllene and squalene, while caryophyllene was a predominant component among the 40 chemicals identified in the ethanol extract. Methylparaben was exclusively present in the ethanol extract, showcasing inhibitory effects on the fungus. This research sheds light on the potential of guava leaf extracts as a sustainable solution for disease management in Chinese kale cultivation. HIGHLIGHTS Ethanolic extract of guava leaf at 3,000 ppm completely inhibits the pathogen Pythium aphanidermatum. Seed coated with ethanol-extracted guava leaf extract at concentrations of 1,500 and 3,000 ppm reduced damping-off disease incidence in Chinese kale in greenhouse trials. Chemical analysis via GC-MS revealed diverse compounds in guava leaf extracts, with notable constituents such as copaene, β-caryophyllene, calamenene and caryophyllene oxide in the hexane extract, β-caryophyllene and squalene in the ethyl acetate extract and caryophyllene predominance in the ethanol extract. Identification of methylparaben exclusively in the ethanol extract suggests its potential inhibitory effects on the fungus. This study underscores the promising potential of guava leaf extracts as a sustainable solution for disease management in Chinese kale cultivation, offering insights into alternative methods for controlling damping-off disease. GRAPHICAL ABSTRACT